2014
DOI: 10.1111/jth.12531
|View full text |Cite
|
Sign up to set email alerts
|

Antigen levels of coagulation factor XII, coagulation factor XI and prekallikrein, and the risk of myocardial infarction and ischemic stroke in young women

Abstract: To cite this article: Siegerink B, Rosendaal FR, Algra A. Antigen levels of coagulation factor XII, coagulation factor XI and prekallikrein, and the risk of myocardial infarction and ischemic stroke, in young women. J Thromb Haemost 2014; 12: 606-13.Summary. Background: High levels of activated proteininhibitor complexes of the intrinsic coagulation proteins are associated with ischemic stroke (IS) but not with myocardial infarction (MI). This study was aimed at determining whether the antigen levels of coagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 38 publications
5
44
3
1
Order By: Relevance
“…Therefore, levels of these complexes do not necessarily correlate with fXII:c or fXII:Ag levels and, indeed, recent data from the RATIO study have indicated that high fXII antigen levels do not correlate with activated protein-inhibitor complexes. 34 Furthermore, as allued to previously, the consequences of moderate and severe fXII deficiency may be very different. 15 …”
Section: Fxiimentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, levels of these complexes do not necessarily correlate with fXII:c or fXII:Ag levels and, indeed, recent data from the RATIO study have indicated that high fXII antigen levels do not correlate with activated protein-inhibitor complexes. 34 Furthermore, as allued to previously, the consequences of moderate and severe fXII deficiency may be very different. 15 …”
Section: Fxiimentioning
confidence: 99%
“…25 Unlike the case with fXII, the use of an antigen assay to measure plasma fXI levels (fXI:Ag) was in agreement with the conclusion using enzymeinhibitor complexes. 34 Therefore, the available data overall seem to support a link between high fXI levels and IS risk.…”
Section: Fximentioning
confidence: 99%
See 3 more Smart Citations